Identification of a torradovirus-encoded protein that complements the systemic movement of a potexvirus lacking the TGB3 gene - Jiménez Polo, Jenyfer (2018)
Cassava torrado-like virus (CsTLV, Family Secoviridae) is found in mixed virus infections associated with severe disease symptoms in leaves and roots of cassava (Manihot esculenta Crantz, Euphorbiaceae), which is an important staple food crop for Africa, Asia and Latin America. The virus has been reported in Colombia, Peru and Argentina, where it has a significant effect on the accumulation of total sugars in cassava storage roots. CsTLV encodes an atypical Maf/HAM1 domain not found in other torradovirus genomes, but is present in heterologous viruses of the family Potyviridae also infecting euphorbiaceous hosts. Most viruses encode RNA silencing suppressors (RSS) to counteract the RNA silencing-based plant defense system. However no RSS has been yet identified in torradoviruses. To advance the characterization of CsTLV, agroinfiltration in Nicotiana benthamiana leaves of different viral genes was carried out using GFP as a reporter. Like the Maf/HAM1 domain found in Cassava brown streak virus (CBSV; Genus: Ipomovirus), the one encoded by CsTLV did not show RSS activity. On the other hand, we found that agroinfiltration of RNA2-ORF1 had a significant effect in the establishment of systemic infection by Cassava virus X (CsVX; Genus: Potexvirus), a virus lacking one of the Triple Gene Block genes (TGB3), which is involved in potexvirus movement. Although we observed that single infection of CsTLV increased the expression of GUS in of GUS-transgenic cassava lines, none of the CsTLV genes in this study showed RSS activity.